Interplay between metamorphic strengthening and structural softening in inclusion‐bearing layered rocks. (16th May 2013) - Adamuszek, Marta; Dabrowski, Marcin; Schmid, Daniel W.
Abstract We employ numerical and analytical methods to investigate the effect of the presence of rigid porphyroblasts such as garnets on layer strengthening and the folding instability. We use a 50% fraction of non‐overlapping, circular‐shaped inclusions with a wide size distribution. These inclusions cause a fourfold effective viscosity increase and can significantly promote the folding instability. This is not only due to the increased viscosity but also due to the layer interface roughness generation driven by relative movement of inclusions. The increase in layer viscosity promotes strengthening of the whole system. However, with progressive fold development, the system undergoes an effective softening that may counteract the strengthening effect of the porphyroblast growth.